Coloration and structure behavior after silver and copper nanoparticles formation in soda lime glass: Farb‐ und Strukturverhalten von Kalk‐Natron‐Glas nach der Bildung von Silber‐ und Kupfernanopartikeln. Issue 11 (5th December 2017) - Chorfa, A.; Belkhir, N.; Belbali, A.; Rubio, F.; Rubio, J.
Abstract: In this work, an ion exchange non‐conventional process commonly called ancient painting process without using molten salts is used as a method for glass coloring. In this process of coloration, a mixture of metallic particles with kaolin and arabic adhesive is applied on the soda lime glass surface. Afterwards, the painted glass is submitted to the heat treatment to obtain the color. A comparative study is carried out in order to investigate the diffusion of metallic nanoparticles (silver and copper) in soda lime glasses depending on several parameters as the concentration and composition of stain spread on glass, and the heat treatment temperature. Characterization of the composition and structure of the painted glasses is performed by UV‐visible spectroscopy. In addition, nanoindentation and scanning electron microscopy (SEM) with energy dispersive X‐ray analysis (EDS) techniques are used to determine the penetration of metallic nanoparticles into glass. The obtained result shows that the coloration of painted glass differs and depends on the concentration and the kind of the mixture of the paw. Moreover, it was found that the effect of the heat treatment temperature is primordial on the formation and diffusion of metallic nanoparticles.